The role and portrayalof the king in the Esther narrative : a narratological-synchronic reading of the Masoretic text of the Esther narrative - Le Roux, J.H. (Jurie Hendrik), 1944- (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 1999.